The Effect of Computer-Assisted Instruction on Achievement and Attitudes Toward Fundamentals of Algebra among College Freshmen - T. Garcia, Ph.D, AURORA; I. ENURAH, NADEZHDA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)